2016
DOI: 10.1038/nbt.3436
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of the PROPATRIA study and its implications for probiotic therapy

Abstract: The PROPATRIA (Probiotics in Pancreatitis Trial) study was a multicenter, double-blind, placebo-controlled clinical trial that aimed to reduce infectious complications in patients with predicted severe acute pancreatitis by the enteral use of a multispecies probiotic preparation. An unprecedented 24 of 152 patients (16%) in the group receiving probiotics died versus 9 of 144 (6%) in the placebo group. This high mortality rate in the probiotic-treated group contrasts strongly with observations from a previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 20 publications
0
40
0
5
Order By: Relevance
“…The colleagues associated high mortality in PROPATRIA study with lethal combination of proteolytic enzymes of pancreas and high level of lactic acid caused by bacterial fermentation of carbohydrates as a key factor related to intake of probiotics. Nevertheless, authors suggest that a probiotic therapy may not be counterindicated for the prevention of secondary infections associated with acute pancreatitis, provided that future clinical studies start probiotic therapy early as possible and prevent bacterial overgrowth not only of patient's own intestinal flora but also the dose of probiotic bacteria [38].…”
Section: Microbiome-oriented Therapy: How To Keep Balance?mentioning
confidence: 99%
“…The colleagues associated high mortality in PROPATRIA study with lethal combination of proteolytic enzymes of pancreas and high level of lactic acid caused by bacterial fermentation of carbohydrates as a key factor related to intake of probiotics. Nevertheless, authors suggest that a probiotic therapy may not be counterindicated for the prevention of secondary infections associated with acute pancreatitis, provided that future clinical studies start probiotic therapy early as possible and prevent bacterial overgrowth not only of patient's own intestinal flora but also the dose of probiotic bacteria [38].…”
Section: Microbiome-oriented Therapy: How To Keep Balance?mentioning
confidence: 99%
“…Коллеги ассоциировали высокую летальность в исследовании PROPATRIA со смертельной комбинацией протеолитических ферментов поджелудочной железы и высоким уровнем молочной кислоты в результате бактериальной ферментации углеводов как ключевого фактора, связанного с приемом пробиотиков. При этом авторы считают, что пробиотическая терапия не является противопоказанием для профилактики вторичных инфекций, связанных с острым панкреатитом, при соблюдении ряда условий: раннего начала пробиотической терапии (сразу после первого появления симптомов болезни), ограничения поставки ферментируемых углеводов и предотвращения чрезмерного роста собственной кишечной флоры пациента [24].…”
Section: лечебные подходы к коррекции микробиотыunclassified
“…A wrong administration or dose for patients with a compromised immune system may cause bacterial sepsis by blood infection . Some studies have reported an increase in human mortality due to the consumption of multispecies probiotic foods (Figure ) . However, their beneficial effects can still be the future of biotechnology.…”
Section: Probiotic Potential Of Lalmentioning
confidence: 99%
“…105 Some studies have reported an increase in human mortality due to the consumption of multispecies probiotic foods (Figure 3). 106,107 However, their beneficial effects can still be the future of biotechnology.…”
Section: Production Of Antimicrobial Compounds By Lalmentioning
confidence: 99%